Principal Academic Supervision Management in Improving Teacher Performance - Aah Khoriah (Generasi, 2026)
Background: Academic supervision management by school principals plays a crucial role in improving teacher performance, particularly in enhancing instructional quality and professional competence in primary education institutions.Objective: This study aims to describe the management of academic supervision conducted by school principals in improving teacher performance at SDIT Ibnu Khaldun.Method: This research employs a qualitative approach with a case study design. The primary data were obtained through in-depth interviews with the school principal. Data were analyzed descriptively using stages of data reduction, data presentation, and conclusion drawing.Findings and Implications: The findings reveal that academic supervision management is implemented through four main stages: planning, organizing, implementing, and evaluating. In the planning stage, the principal focuses on strengthening teacher competence, preparing teaching tools, and aligning instruction with the school’s vision. In organizing, the principal fosters collaboration with teachers and curriculum administrators while assigning roles based on competencies. Implementation involves learning assistance, strengthening learning communities, lesson study, and collaborative learning practices. Evaluation includes observation, reflection, monitoring, and follow-up actions such as improving lesson plans and providing further training. These practices contribute positively to teacher performance, particularly in instructional planning, teaching innovation, professional collaboration, and adaptability to student needs.Conclusion: The study concludes that effective management of academic supervision by school principals significantly enhances teacher performance and supports continuous professional development.